Impacts of health expenditure financing on infant mortality and diminishing returns: Implications for Sub-Saharan Africa - Yoorim Bang; Jinhwan Oh (Global Business & Finance Review (GBFR), 2020)
Purpose: This study examines the impacts of health expenditures on infant mortality. Design/methodology/approach: This study is based on a comprehensive panel data of 100 countries (31 developed and 69 developing countries) for 18 years (2000-2017) and, based on the Hausman Test, applies fixed effect analyses. Findings: Not only a negative relationship between health expenditures and the infant mortality rate but its diminishing returns are found. This pattern turns out to be stronger in developing countries, particularly in Sub-Saharan Africa. It appears that a country can easily target the most needed class or region to effectively minimize infant mortality given a limited amount of health expenditure, but that same amount may not suffice in reaching defined goals. Research limitations/implications: This implies that the rising amounts of health expenditure would be needed if countries seek to decrease infant mortality at the same rate as they had previously done. To expedite a response, multi-agency or multi-national coordination is essential, and an effective means of mobilizing resources, such as basket funding or program-based approaches, would be desirable. Originality/value: With an up-to-date dataset, this study confirms the effectiveness of health expenditure disbursement with its diminishing returns, which may shed light to developing countries in designing relevant policies.
Keywords: 650; Health Expenditure; Infant Mortality; Diminishing Returns; Sub-Saharan Africa